Successful Surgical Management of a Coincidence of Three‐Vessel Coronary Artery Disease, Severe Carotid Atherosclerosis, and Carotid Paraganglioma: A Case Report and Literature Review - Pouya Ebrahimi; Tooba Akbari; Aysan Nozheh; Amir Nasrollahizadeh; Sepide Javankiani; Pedram Ramezani; Mohammad Hossein Mandegar; Sagar N. Doshi; Farhan Shahid (Clinical Case Reports)
ABSTRACT Screening for carotid atherosclerosis is mandatory before coronary artery bypass graft (CABG). Incidental pathologies, such as carotid paraganglioma, may be discovered rarely, complicating management. A 53‐year‐old woman with three‐vessel coronary artery disease and exertional chest pain underwent routine carotid ultrasound, revealing “> 90% stenosis of the left external carotid artery and a 1.8 × 1.2 × 1.0 cm mass at the carotid bifurcation, classified as Shamblin II.” She reported a painless, pulsatile left‐neck mass but no cranial nerve deficits. Preoperative coil embolization was not performed due to manageable intraoperative control of the vascular supply. The patient successfully underwent simultaneous CABG, carotid endarterectomy, and tumor excision; histopathology confirmed paraganglioma. Patients with multivessel coronary disease often harbor severe carotid atherosclerosis, warranting concomitant endarterectomy at the time of CABG. Pre‐operative imaging may unmask incidental carotid body tumors (e.g., a 1.8 × 1.2 × 1.0 cm Shamblin II paraganglioma), which require surgical excision and histopathologic assessment to guide optimal multidisciplinary care.